Using Cognitive Diagnostic Assessment to Inform Differentiated Instruction in Elementary Place Value Concepts - Dhesta Nurdana Puspita; Wiryanto; Tatag Yuli Eko Siswono (Journal of Innovation and Research in Primary Education, 2026)
Place value understanding is a fundamental prerequisite for advanced mathematical learning, yet elementary students often demonstrate heterogeneous comprehension that challenges uniform teaching approaches. This study examines the use of cognitive diagnostic assessment (CDA) to identify student learning profiles and inform differentiated instruction in Indonesian elementary mathematics. A mixed-methods descriptive design involved 12 fourth-grade students at SD Negeri Jubellor, East Java. Data were collected through structured interviews and a five-item diagnostic test on place value concepts. Psychometric properties were analyzed using ANATES, while student performance was categorized into high (≥98%), moderate (64–97%), and low (<64%) understanding levels. The assessment showed strong psychometric quality with item correlations between 0.815–0.876 (p<0.01) and high reliability (α=0.87). Difficulty analysis indicated balanced distribution, with one very easy item (20%) and four moderately difficult items (80%). Results revealed heterogeneous profiles: 25% low understanding, 42% moderate, and 33% high. Students with low understanding struggled with reading multi-digit numbers and place value beyond thousands. Those at the moderate level demonstrated competency up to ten thousands but faced difficulties at hundred thousands and contextual applications. High-achieving students mastered place value comprehensively, including real-world applications. These findings demonstrate that CDA not only identifies specific learning gaps but also provides actionable insights for planning targeted instructional pathways. Strengthening this diagnostic–instructional alignment is essential to ensure responsive teaching that supports all learner profiles, particularly in bridging conceptual gaps among students at the moderate and low understanding levels.